Pengaruh Tingkat Margin terhadap keputusan dalam memilih pembiayaan bank syariah dengan religiusitas sebagai variable moderasi - Putri, Siska lusia; Azman, Heru Aulia; Sari, Puti Embun (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
The customer's decision to choose the financing product to use is a form of customer confidence. This belief arises because customers are satisfied with the financing products they will use. This research aims to determine the influence of margin levels on customers' decisions to choose financing products with religiosity as a moderating variable. The research population is all customers who take out financing at Sharia Bank. The research sample was taken using purposive sampling as many as 96 respondents. The research results conclude that the margin level has a positive but not significant effect on financing decisions and religiosity moderates the relationship between the margin level and financing decisions but is not significant